2019
DOI: 10.14744/tjtes.2019.78002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early femoral nerve block intervention on preoperative pain management and incidence of postoperative delirium geriatric patients undergoing trochanteric femur fracture surgery: a randomized controlled trial

Abstract: BACKGROUND: Hip fracture is a common clinical problem which causes severe pain in geriatric patients. However, severe pain following fracture may bring on mental disorders and delirium. A neuroinflammatory response with IL-6 and IL-8 has been shown to be associated with the pathophysiology of delirium. In this study, our primary hypothesis is that preoperative femoral nerve block (FNB) intervention in geriatric patients will more effectively attenuate pain following trochanteric femur fracture than the preoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 24 publications
0
46
1
Order By: Relevance
“…[27][28][29] Another important situation is the anesthesia type and pain management administered to the patient. [30] Different from the literature, in our study, there was no significant correlation found between the form of anesthesia and mortality. There are publications stating that general anesthesia is linked to more mortality in this patient group; however, it can be said that this was observed more in patients with high risk related to cardiac causes.…”
Section: Discussioncontrasting
confidence: 99%
“…[27][28][29] Another important situation is the anesthesia type and pain management administered to the patient. [30] Different from the literature, in our study, there was no significant correlation found between the form of anesthesia and mortality. There are publications stating that general anesthesia is linked to more mortality in this patient group; however, it can be said that this was observed more in patients with high risk related to cardiac causes.…”
Section: Discussioncontrasting
confidence: 99%
“…The trials were published from 2010 to 2021 and the number of randomised participants ranged from 20 to 198. Seven trials investigated the femoral nerve block [ 15 , 16 , 18 , 20 , 21 , 23 , 28 ] and six investigated the fascia iliaca compartment block [ 17 19 , 22 , 27 , 29 ]. Of the 12 trials, four sought to blind the patients by using a type of sham block [ 15 , 17 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 trials, four sought to blind the patients by using a type of sham block [ 15 , 17 , 19 , 20 ]. Eight trials had a single shot US-PNB as intervention [ 15 18 , 20 , 23 , 27 , 29 ] whereas four trials administered an initial bolus before placing a catheter for continuous infusion [ 19 , 21 , 22 , 28 ]. One study described testing for block success [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate pain control was highlighted as a potential contributor to risk of delirium development (Chuan et al, 2020; Martocchia et al, 2015; Patel et al, 2018; Poeran et al, 2020; Uysal et al, 2020). However, control of pain with morphine in the post‐operative period was found to triple the risk of developing delirium (Smith et al, 2017).…”
Section: Resultsmentioning
confidence: 99%